What do scholarly channels and resources do authors trust to read, cite and publish in? : A Malaysian study - Abrizah, Abdullah; Badawi, F.; Zoohorian-Fooladi, N.; Nicholas, D.; Jamali, H.R.; Norliya, A.K. (2014)
The paper provides the results of the first phase of the research project Trust and Authority in Scholarly Communications: The Periphery of World Scholarship in the Digital Era conducted in Malaysia. It provides for an examination of the behaviours and attitudes of academic researchers as producers and consumers of scholarly information resources in today's scholarly digital environment; with respect to how they determine authority and trustworthiness in the sources they use, cite, and publish in. This first phase utilised focus groups to obtain this information. Five focus groups were conducted in three universities in Kuala Lumpur involving a total of 48 science and social science researchers cum authors. Findings indicate that peer-reviewed journals are still the central to the authors, however they seem to have more freedom in relation to journals they read and cite, compared to publish. Overall, authors view that scholarly resources that are current, relevant, authored by credential scholars, peer-reviewed, having credible reference lists, published by reputable journals, and having online presence are fit for scholarly utilisation. The extent to which authors are prepared to believe that the scholarly information source and channel are trustworthy for publication rely on it in view of its impact, indexation status, reputation, peers' recommendation, accessibility and visibility, and authority's approval. New forms of communication channels such as social media or new journal models are not much used in formal scholarly communication or perhaps on the verge of being more used. The focus groups provided the direction for. questionnaires and interviews that would follow. The paper also discusses the implication of the findings to academic librarians towards delivering the right services to meet the needs of the scholarly community.